EXAFS studies of the trapping site structure for molecules isolated in cryogenic matrices: Low-Temperature Physics and Chemistry in Cryomatrice - Roubin, P.; Varin, S.; Cre&#61449pin, C.; Gauthier-Roy, B.; Flank, A.-M.; Lagarde, P.; Tenegal, F. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2000)
We present here results concerning the first attempt of determining the trapping site structure of molecules isolated in inert matrices at low temperature by the EXAFS (Extended X-ray Absorption Fine Structure) method. The experiments have been performed at the K edge of argon, silicon, sulfur, and chlorine for pure solid argon, and for SiH4, OCS and HCl isolated in different cryogenic matrices. The EXAFS technique is sensitive to the local environment around the absorbing atom and the spectral features induced by the matrix material (Ar, Xe, N2 and CH4) are clearly evidenced here. The data allow a characterization of the double substitutional site for OCS in argon and xenon while no structure can be determined for the accommodation of SiH4 in argon. A discussion of the best choice for the guest/host system to obtain a good EXAFS signal is included.